Clara Guillén Marín. Migrants in Contemporary Spanish Film. Rouledge, 2018. - Alfonso Bartolomé (Studies in 20th & 21st Century Literature, 2019)
Review of Clara Guillén Marín. Migrants in Contemporary Spanish Film. Rouledge, 2018.
Keywords: migrants; contemporary Spanish film